Biopolymer nanofibrils: Structure, modeling, preparation, and applications - Ling, Shengjie; Chen, Wenshuai; Fan, Yimin; Zheng, Ke; Jin, Kai; Yu, Haipeng; Buehler, Markus J.; Kaplan, David L. (Progress in polymer science, 2018)
[Display omitted] Biopolymer nanofibrils exhibit exceptional mechanical properties with a unique combination of strength and toughness, while also presenting biological functions that interact with the surrounding environment. These features of biopolymer nanofibrils profit from their hierarchical structures that spun angstrom to hundreds of nanometer scales. To maintain these unique structural features and to directly utilize these natural supramolecular assemblies, a variety of new methods have been developed to produce biopolymer nanofibrils. In particular, cellulose nanofibrils (CNFs), chitin nanofibrils (ChNFs), silk nanofibrils (SNFs) and collagen nanofibrils (CoNFs), as the four most abundant biopolymer nanofibrils on earth, have been the focus of research in recent years due to their renewable features, wide availability, low-cost, biocompatibility, and biodegradability. A series of top-down and bottom-up strategies have been accessed to exfoliate and regenerate these nanofibrils for versatile advanced applications. In this review, we first summarize the structures of biopolymer nanofibrils in nature and outline their related computational models with the aim of disclosing fundamental structure-property relationships in biological materials. Then, we discuss the underlying methods used for the preparation of CNFs, ChNFs, SNFs and CoNFs, and discuss emerging applications for these biopolymer nanofibrils.